2018
DOI: 10.1128/jvi.01613-17
|View full text |Cite
|
Sign up to set email alerts
|

Axl Can Serve as Entry Factor for Lassa Virus Depending on the Functional Glycosylation of Dystroglycan

Abstract: Fatal infection with the highly pathogenic Lassa virus (LASV) is characterized by extensive viral dissemination, indicating broad tissue tropism. The major cellular receptor for LASV is the highly conserved extracellular matrix receptor dystroglycan (DG). Binding of LASV depends on DG's tissue-specific posttranslational modification with the unusual O-linked polysaccharide matriglycan. Interestingly, functional glycosylation of DG does not always correlate with viral tropism observed The broadly expressed phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
62
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 103 publications
11
62
1
Order By: Relevance
“…In this study, we found that that PtdSer receptor TIM-1 mediates the entry of either LCMV or vesicular stomatitis virus (VSV) pseudovirions bearing LASV GP but only when ␣DG either is not expressed or does not contain the necessary LARGE-dependent alterations of the O-linked glycans. This is consistent with findings that the high-affinity interactions of LASV GP and ␣DG prevail over lower-affinity PtdSer/PtdSer receptor interactions (49). Furthermore, we found that the TAM receptor Axl was unable to serve as a receptor for LASV pseudovirions in HEK 293T and Vero cells, irrespective of the status of ␣DG in these cells.…”
Section: Importancesupporting
confidence: 92%
“…In this study, we found that that PtdSer receptor TIM-1 mediates the entry of either LCMV or vesicular stomatitis virus (VSV) pseudovirions bearing LASV GP but only when ␣DG either is not expressed or does not contain the necessary LARGE-dependent alterations of the O-linked glycans. This is consistent with findings that the high-affinity interactions of LASV GP and ␣DG prevail over lower-affinity PtdSer/PtdSer receptor interactions (49). Furthermore, we found that the TAM receptor Axl was unable to serve as a receptor for LASV pseudovirions in HEK 293T and Vero cells, irrespective of the status of ␣DG in these cells.…”
Section: Importancesupporting
confidence: 92%
“…Here, we discovered that by inducing actin remodeling GAS6 stimulation triggers macropinosome formation, and GAS6-AXL complexes localize to macropinosomes indicating that a fraction of AXL is internalized via macropinocytosis. Thus, our data provide a mechanistic explanation for previous virology studies reporting that AXL might contribute to macropinocytic uptake of Lassa and Ebola viruses upon infection (Fedeli et al, 2018;Hunt et al, 2011).…”
Section: Discussionsupporting
confidence: 69%
“…The conserved and widely expressed receptor for extracellular matrix proteins, α-dystroglycan (α-DG), is a main receptor for Old World (OW) mammarenaviruses, such as lymphocytic choriomeningitis virus (LCMV) and Lassa virus (LASV) [38]. Secondary alternative receptors, including members of the Tyro3/Axl/Mer and T-cell immunoglobulin mucin (TIM) receptor families may account for LASV and LCMV infection of cells lacking fully glycosylated α-DG [44,45]. Cell entry of the OW hemorrhagic fever (HF) mammarenavirus Lujo virus (LUJV) is mediated by neuropilin (NRP)-2, a cell-surface receptor for semaphorins [46].…”
mentioning
confidence: 99%